1989
DOI: 10.1161/01.res.64.4.676
|View full text |Cite
|
Sign up to set email alerts
|

The pH of spontaneously beating cultured rat heart cells is regulated by an ATP-calmodulin-dependent Na+/H+ antiport.

Abstract: We investigated the mechanisms by which spontaneously beating cultured rat ventricular cells regulate intracellular pH (pHi). Specifically, the relative contributions of the Na+/H+ antiport, Cl-/HCO3- exchange, ATP, and calmodulin-dependent processes in regulating the pHi of cells loaded with the intracellular fluorescent pH indicator BCECF were investigated. The pHi of ventricular cells bathed in HEPES-buffered medium averaged 7.30 +/- 0.02. Subsequent exposure of the cells to CO2-HCO3- -buffered medium resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0
1

Year Published

1992
1992
2002
2002

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(38 citation statements)
references
References 34 publications
2
35
0
1
Order By: Relevance
“…The possibility that \V7 wvas decreasing myofilament Ca2+ sensitivity by producing an intracellular acidosis (e.g. see Orchard & Kentish, 1990) by inhibiting the Na+-H+ exchange mechanismn (Weissberg et al 1989) seems unlikely because our results with BC(ECF-loaded myocytes suggest that neither the magnitude nor time course of the change of p14j in W7 were appropriate to explain the observed changes in the size of the twitch.…”
Section: Oj Oumentioning
confidence: 81%
“…The possibility that \V7 wvas decreasing myofilament Ca2+ sensitivity by producing an intracellular acidosis (e.g. see Orchard & Kentish, 1990) by inhibiting the Na+-H+ exchange mechanismn (Weissberg et al 1989) seems unlikely because our results with BC(ECF-loaded myocytes suggest that neither the magnitude nor time course of the change of p14j in W7 were appropriate to explain the observed changes in the size of the twitch.…”
Section: Oj Oumentioning
confidence: 81%
“…27 Indeed, ATP depletion results in decreased activity of Na ϩ /H ϩ exchange by all 3 exchanger isoforms. 25,28 Although it has been suggested that ATP depletion affects basal Na ϩ /H ϩ exchanger activity by decreasing phosphorylation of the antiporter, 22,45,46 this concept has been challenged, since ATP depletion rapidly inhibits the Na ϩ /H ϩ exchanger in NHE-1-transfected fibroblasts without affecting NHE-1 phosphorylation. 27 The mechanism of ATP depletion may be important in determining the effect on exchanger activity.…”
Section: Discussionmentioning
confidence: 99%
“…Operation of the Na+-H+ antiporter depends upon the Na gradient but metabolic energy may contribute to its pumping ability and modulation by [H+], (Cassel et al, 1986;Grinstein and Rothstein, 1986;Weissberg et al, 1989;Wakabayashi et al, 1992). With reduction of cellular ATP, the exchanger decreases its affinity for hydrogen at the internal regulatory site (Cassel et al, 1986;Wakabayashi et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Indirect evidence suggests that protein kinase C may stimulate the antiporter via a phosphorylationdependent regulatory site in neuroblastoma cells and lymphocytes (Moolenaar et al, 1984;Grinstein et al, 1985a). Regulatory phosphorylation sites have also been implicated by antiporter sensitivity to calmodulin antagonists in cardiac ventriculocytes (Weissberg et al, 1989). With the loss of highenergy phosphate sources that accompanies excitotoxic damage (Kass and Lipton, 1982;Rothman et al, 1987), this regulatory site may become dephosphorylated, resulting in a slower rate of hydrogen extrusion.…”
Section: Discussionmentioning
confidence: 99%